Is Milrinone Effective for Infants with Mild-to-Moderate Congenital Diaphragmatic Hernia? - Mears, Michelle; Yang, Michelle; Yoder, Bradley A. (American Journal of Perinatology, 2020)
Objective Pulmonary hypertension with left ventricular dysfunction commonly occurs in congenital diaphragmatic hernia (CDH). Milrinone, a phosphodiesterase-III inhibitor with lusitropic and vasodilator effects, is used in up to 30% of CDH infants across the United States. No randomized trials have tested the efficacy or safety of milrinone in CDH neonates.Study Design We performed a paired retrospective analysis of CDH infants to assess the efficacy of milrinone treatment (N = 24 pairs). Efficacy was assessed by change in oxygenation index (OI) and calculated pulmonary artery pressure (PAP). We evaluated safety on the basis of risks factors such as nonoperative bleeding, dysrhythmia, hypokalemia, and thrombocytopenia.Results The median age of milrinone initiation was 18 hours (interquartile range [IQR]: 9–38) and the median duration was 127 hours (IQR: 95–194). PAP did not change from the baseline of 49 ± 11 mm Hg (milrinone) and 53 ± 11 mm Hg (no milrinone; p = 0.327). Baseline OI was 9.6 ± 6.5. There was a similar decrease in OI (median [IQR]; milrinone: 58% [16–74]; vs. no milrinone: 65% [50–71]; p = 0.221 between groups; p < 0.005 within groups). Baseline left ventricle measurements were similar. Both groups showed significant improvement over time. No adverse events were noted.Conclusion In OI-matched untreated neonates with mild-to-moderate CDH, milrinone use was associated with neither improved OI, PAP, or left ventricular measurements, nor adverse events. Study limitations warrant prospective randomized controlled trials.
Keywords: milrinone; congenital diaphragmatic hernia; pulmonary hypertension; neonate